2015
DOI: 10.1155/2015/965257
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exertional Compartment Syndrome in a High School Soccer Player

Abstract: Chronic exertional compartment syndrome (CECS) is a relatively rare condition that affects young adult athletes and often causes them to present to the emergency department. If left untreated, those who continue to compete at high levels may experience debilitating leg pain. Physicians may have difficulty differentiating CECS from other syndromes of the lower leg such as medial tibial stress syndrome, stress fractures, and popliteal artery entrapment. The gold standard for diagnosing CECS is intramuscular comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…One of the most utilised is that developed by Mubarak [16]: a fasciotomy of the anterior and lateral compartments via a 10cm incision. While newer techniques are mini-invasive either via an endoscopic or cutaneous mini-accesses [9][10][11][12][13][14][15][16][17]. These more modern approaches produce results similar to those of interventions using more ample accesses [18].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most utilised is that developed by Mubarak [16]: a fasciotomy of the anterior and lateral compartments via a 10cm incision. While newer techniques are mini-invasive either via an endoscopic or cutaneous mini-accesses [9][10][11][12][13][14][15][16][17]. These more modern approaches produce results similar to those of interventions using more ample accesses [18].…”
Section: Discussionmentioning
confidence: 99%
“…Other modalities to be considered include stretching and strengthening of the lower extremity musculature, massage of the hypertonic musculature compartment, icing and the use of anti-inflammatory medications. [ 22 23 ]…”
Section: What Can I Do In My Practice?mentioning
confidence: 99%
“…Flick and Flick [5] explain that diagnosis of ECS proves to be difficult as there are no clinically established criteria for diagnosis. Differential diagnoses such as Medial Tibial Stress Syndrome (MTSS), peroneal nerve entrapment, periostitis, anterior tibialis contusions, and stress fractures of tibia need to be ruled out [5,6]. Therefore, delays in early diagnosis and treatments can be detrimental to the athlete as symptoms increase and the possibility of irreversible nerve/ tissue impairment is present.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, delays in early diagnosis and treatments can be detrimental to the athlete as symptoms increase and the possibility of irreversible nerve/ tissue impairment is present. Moreover, it has been found that there can be a 22-month delay in diagnosis due to athletes' self-limiting or modifying activity based on pain, which can hinder the diagnostic process [4,6].…”
Section: Introductionmentioning
confidence: 99%